A comparative study on factors affecting time to cover cracking as a service life indicator. (28th February 2018) - Chen, Fangjie; Baji, Hassan; Li, Chun-Qing
Highlights: A full review on time to cover cracking models has been conducted. Sensitivity analysis to identify the most influential factors on time to cover cracking is presented. The porous zone and the properties of rust are the most influential factors for time to cover cracking. There is high uncertainty in prediction of time to cover cracking as a service life indicator. Abstract: Corrosion of steel in reinforced concrete structures has been a major worldwide problem. The time to cover cracking plays a key role in assessment of serviceability of reinforced concrete structures subjected to corrosion. A large number of analytical, numerical, and empirical models have been developed to predict the time to time to cover cracking. In addition, extensive experiments have been conducted in order to verify the developed models. In this paper, an overview of the existing models is presented. A large experimental database of reported data on time to cover cracking is collated. Performance of four analytical models taken from the available literature is then examined using the established experimental database. Sensitivity analysis followed by a probabilistic study is carried out to identify the factors affecting time to cover cracking as a service life indicator by means of the selected models. The results from sensitivity analysis show that the porous zone and the properties of rust are the most influential factors for time to cover cracking. It is also shown that there is high uncertainty in predicting service life of reinforced concrete structures based on time to cover cracking.